Post-industrial Technologies in the Economy of the North-West of Russia - Rumyantsev, Aleksey A. (Economy of Regions, 2021)
A new class of post-industrial technologies is gradually being introduced into various sectors of the economy. However, the lack of application experience may hinder their spread. The article examines two issues of post-industrial technologies. Firstly, there is a need to identify promising (advanced) production technologies that are fundamentally different from traditional industrial technologies. Secondly, the study aims to assess the current stage of the development and application of these technologies on the example of the North-West of Russia. This assessment may be of interest for understanding the advantages of the technologies’ use and the possibility of their distribution. The article describes the application of post-industrial technologies, giving examples of their use for attracting business and expanding the functions and responsibilities of regional authorities. Based on the structural method, post-industrial technologies were divided into various types: renewable energy sources, nanotechnologies, and information and communication technologies (ICTs). The article shows their distribution across the regions of the North-West of Russia, companies that implement post-industrial technologies and their products. The paper reveals the characteristics and definition of post-industrial technologies, as well as the specificity of their application in regions. In the North-West of Russia, regions with large resources in wind and water as well as partly solar energy sectors use renewable energy sources applying hybrid power systems (wind/solar, wind/solar/diesel) to supply power to remote small villages without centralised electricity systems. Nanotechnology are applied in the production of composite materials, metal-ceramic materials, nanoelectronics, laser cladding. Biotechnologies are used for processing animal waste and resources of the White Sea for the production of compound fertilisers, fast-degradable polymers, and biocomposites. Digital technologies are applied for the development of smart cities, smart power system, digital shipyard, robotics with artificial intelligence elements. The paper identifies the field of business application of postindustrial technologies, highlighting the increasing localisation and individualisation of production due to such technologies. The research results can be used for the elaboration of socio-economic development strategies, recommendations for business structures in the implementation of post-industrial technologies. Further studies should focus on the economic analysis of postindustrial technologies application, their convergence in production processes.